Serum Hyperchloremia as a Risk Factor for Acute Kidney Injury in Patients with St-Segment Elevation Myocardial Infarction Undergoing Percutaneous Coronary Intervention. Issue 1 (1st January 2016) - Patel, Nachiket; Baker, Sarah M.; Walters, Ryan W.; Kaja, Ajay; Kandasamy, Vimalkumar; Abuzaid, Ahmed; Modrykamien, Ariel M.
Abstract : A high serum chloride concentration has been associated with the development of acute kidney injury in critically ill patients. However, the association between hyperchloremia and acute kidney injury (AKI) in patients admitted with ST-segment elevation myocardial infarction (STEMI) treated with percutaneous coronary intervention (PCI) is unknown. A retrospective analysis of consecutive patients admitted with the diagnosis of STEMI and treated with PCI was performed. Subjects were classified as having hyper- or normochloremia based upon their admission serum chloride level. Multivariable logistic regression analyses were employed for the primary and secondary outcomes. The primary analysis evaluated whether high serum chloride on admission was associated with the development of AKI after adjusting for age, diabetes mellitus, admission systolic blood pressure, contrast volume used during angiography, Killip class, and need for vasopressor therapy or intraaortic balloon pump. The secondary analyses evaluated whether high serum chloride was associated with sustained ventricular tachycardia or fibrillation. Of 291 patients (26.1% female, mean age of 59.9 ± 12.6 years, and mean body mass index of 29.3 ± 6.1 kg/m 2 ), 25 (8.6%) developed AKI. High serum chloride on admission did not contribute significantly to the development of AKI (odds ratio, 95%; confidence interval, 0.90 to 1.24). In addition, serum chloride on admission was not significantly associated with sustained ventricular tachycardia or fibrillation after adjusting for demographic and clinical covariates. In conclusion, our study demonstrated no association between baseline serum hyperchloremia and an increased risk of AKI in patients admitted with STEMI treated with PCI.